RYUKYANO/OKINAWANO OU JAPONÊS COMO DILEMA IDENTITÁRIO: da formação do Estado-nação japonês às representações no TikTok - Uechi, Gabriela Franco (2024)
This research was grounded in the hypothesis of constructing a Ryukyuan/Okinawan identity discourse in opposition to the dominant Japanese discourse that categorizes them as Japanese. The historiographical review highlighted the distinction between these two identities. In the analysis, data collected from the TikTok digital content platform were employed, conceptualizing it as a "discursive medium" carrying an ethical world intrinsic to the examined discourses. The methodological and analytical framework of the research was anchored in the notion of "discursive ethos," as explored by Maingueneau (2018; 2020). From the analyzed material, it can be concluded that the Ryukyuan/Okinawan identity discourse is characterized by the cultural particularities of this people, which, even after the period of Japanese colonial assimilation and migratory processes, remains present and distinct from the Japanese national identity discourse.